The Relationship between Mother's Knowledge and Compliance in Giving Vitamin A to Toddlers in the Working Area of the Nusa Indah Health Center, Bengkulu City - Ayudiah, Febra; Rossita, Taufiani (Universitas Dehasen Bengkulu, 2023)
Vitamin A is the most important nutrient because our daily food consumption does not meet the needs of vitamin A in the body, so vitamin A intake is needed from outside the body. Deficiency of vitamin A (VAD) will increase morbidity and even lead to death, complaints that are often obtained when someone suffers from VAD symptoms can be easily attacked by diarrhea, pneumonia, pneumonia, and finally death (Maulina, 2018). This study aims to study the relationship between mother's knowledge and adherence to giving vitamin A to toddlers in the working area of the Nusa Indah Health Center in Bengkulu City. This study used a quantitative design using a cross-sectional analytical survey design. The population in this study were toddlers aged 12-59 months who were recorded at the recapitulation of the Nusa Indah Health Center in Bengkulu City as many as 1164 toddlers in February 2022. The sampling technique used the accidental sampling method with a total sample of 102 people. Data is taken using secondary data and primary data. Data analysis used univariate and bivariate analysis, to determine the closeness of the relationship used the statistical Contingency Coefficient (C) test. The results of the study were: Of the 102 respondents or mothers who had toddlers, there were 44 people with good knowledge, 54 mothers of toddlers who did not comply with giving vitamin A. There was a significant relationship between mother's knowledge and adherence to giving vitamin A at the Nusa Indah Health Center in Bengkulu City, with the relationship category currently.